2004
DOI: 10.1007/s00262-004-0499-7
|View full text |Cite
|
Sign up to set email alerts
|

a-Tocopheryl succinate sensitizes established tumors to vaccination with nonmatured dendritic cells

Abstract: This study demonstrates the potential usefulness of alpha-tocopheryl succinate, an agent nontoxic to normal cell types, as an adjuvant to augment the effectiveness of DC-based vaccines in treating established tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Our laboratory has pioneered studies that have examined the interplay between these VE analogues and cells of the immune system with the goal of harnessing the unique properties of tumour cell killing and T cell activation to generate an effective anti-tumour response. Similar to the previously reported selective toxicity of these VE compounds towards cancer cells compared to noncancerous cells, we have also demonstrated that a-TOS is minimally toxic to murine splenic lymphocytes and dendritic cells (DC) both in vitro (Ramanathapuram et al, 2004) and in vivo (unpublished observations) at concentrations that are toxic to tumour cells.…”
Section: Vitamin E Analogues As Modulators Of the Immune Functionsupporting
confidence: 80%
“…Our laboratory has pioneered studies that have examined the interplay between these VE analogues and cells of the immune system with the goal of harnessing the unique properties of tumour cell killing and T cell activation to generate an effective anti-tumour response. Similar to the previously reported selective toxicity of these VE compounds towards cancer cells compared to noncancerous cells, we have also demonstrated that a-TOS is minimally toxic to murine splenic lymphocytes and dendritic cells (DC) both in vitro (Ramanathapuram et al, 2004) and in vivo (unpublished observations) at concentrations that are toxic to tumour cells.…”
Section: Vitamin E Analogues As Modulators Of the Immune Functionsupporting
confidence: 80%
“…Positive correlation was observed between tumor growth inhibition and INF-ɣ production by T lymphocytes isolated from mice spleens treated with α-TOS+DCs. Anti-cancer activity of α-TOS+DCs was superior to α-TOS resulting in complete tumor regression in some cases [46]. Solubilization of α-TOS in ethanol was replaced by more potentially clinically relevant adjuvant of vesiculated α-TOS formulation.…”
Section: Administration Routes For Delivery Of Liposomal Vitamin E Anmentioning
confidence: 99%
“…Various approaches have been employed for the preparation of delivery systems of VE analogues, especially for well-studied α-TOS. Solubilization of α-TOS in ethanol, dimethylsulfoxide (DMSO) or oil emulsions was used for the application of the drug in mouse tumor models [20,45,46]. However, it has been reported that as few as one or two injections of the therapeutic dose of α-TAM solubilized in DMSO caused rapid death of experimental animals (Balb/c, C57Bl and FVB/N c-neu mice).…”
mentioning
confidence: 99%
“…Unlike vitamin E, a-TOS has been shown to be a potent inducer of apoptosis of a wide range of human and murine cancer cells including human breast, cervical, endometrial, prostate, colon, lung and lymphoid cancer cells (3)(4)(5)(6)(7), while showing limited or no toxicity towards normal cells or transformed nontumorigenic cells (1,5,6). In an in vivo setting using experimental tumor models, a•-TOS has been demonstrated to inhibit the growth of melanoma (8), breast (9), lung (10) and colon (3,11) cancers. One of the major limitations of using a-TOS is its insolubility in aqueous solvents, which makes it unsuitable for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major limitations of using a-TOS is its insolubility in aqueous solvents, which makes it unsuitable for use in humans. Unlike ca-TOS which is soluble only in organic solvents like sesame oil, dimethylsulfoxide or ethanol (3,(8)(9)(10), vesiculated a-TOS (Voa-TOS) is hydrophilic and is generated by the addition of sodium hydroxide and sonication in PBS to form a colloidal suspension (12). This formulation of a-TOS has been shown to inhibit the progression of tumors as well as prolong the survival of tumor-bearing mice (12,13).…”
Section: Introductionmentioning
confidence: 99%